Detrimental effect of mandibular mucormycosis burlesquing as osteosarcoma - Kiran Alam; Shagufta Qadri; Feroz Alam; Shakeba Quadri (Wolters Kluwer Medknow Publications, 2016)
Mucormycosis is an acute, opportunistic infection caused by a saprophytic fungi typically inhabiting the soil or decaying organic matter. It is an invasive and potentially fatal infection caused by fungi of the order Mucorales, which commonly affects structures in the head and neck including air sinuses, orbits, and the brain. We describe our clinical experience of a case of mandibular mucormycosis, developing in a 45-year-old male who had a family history of diabetes. He presented with complaints of pain and foul-smelling discharge from a nonhealing, ulcerative wound at the mandibular alveolus, encompassing the area around the left canine and 1st premolar. The x-ray revealed osteolytic bony lesion with massive destruction of the mandibular ramus. A clinical impression of osteosarcoma was deduced. Surgical curettage was performed; however, the histopathological examination and subsequent treatment with periodic acid-Schiff stain aided in achieving a conclusive diagnosis of mandibular mucormycosis.